ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA LEMBAGA PERKREDITAN DESA (LPD) KECAMATAN BANJARANGKAN - Kepramareni, Putu; Ernawatiningsih, Ni Putu Lisa (Jurnal Riset Akuntansi (JUARA), 2019)
LPD is a village-owned financial institution whose role is to collect and chanel funds to traditional village communities. The company’s ability to make a profit is called profitability. This study aims to determine the effect of growth in savings, deposits, and credit on profitability in LPDs at Banjarangkan sub-district for the period 2015-2017 with using a population of 30 LPDs in Banjarangkan Sub-district and purposive sampling using 15 LPDs as samples in this study. The analytical method used is multiple linear regression analysis which is equipped with descriptive statistics, classic assumption tests and feasibility test modes. Hypothesis testing is done using the F test and t test. The results of this study indicate that the growth of saving and credit growth did not affect profitability in LPDs in Banjarangkan Sub-district for the period 2015-2017, while deposit growth had a positive effect on profitability in LPDs in Banjarangkan Sub-district for the period 2015-2017.